Potent Molecular Feature-based Neutralizing Monoclonal Antibodies as Promising Therapeutics Against SARS-CoV-2 Infection - Kombe Kombe, Arnaud John; Zahid, Ayesha; Mohammed, Ahmed; Shi, Ronghua; Jin, Tengchuan (Frontiers in Molecular Biosciences, 2021)
The 2019-2020 winter transition was marked by the emergence of a new coronavirus (SARS-CoV-2) related disease (COVID-19), which started in Wuhan, China. Its high human-to-human transmission ability led to a worldwide spread within few weeks and has caused substantial human loss. Unfortunately, aside from the mechanical antiviral control approach, the drug repositioning, and the use of COVID-19 convalescent plasmas (CPs), there are neither effective antiviral drugs nor available vaccines against this novel SARS-CoV-2. However, besides CP, an alternative and effective treatment option for such an infectious disease would include pure anti-viral neutralizing monoclonal antibodies (NmAbs), which can block the virus at specific molecular targets from entering cells by inhibiting virus-cell structural complex formation, with more safety and efficiency than the CP. Indeed, there is a lot of molecular evidence about the protector effect and the use of molecular feature-based NmAbs as promising therapeutics to contain COVID-19. Thus, from the scientific publication database screening, we here retrieved antibody-related papers and summarized the repertory of characterized NmAbs against SARS-CoV-2, their molecular neutralization mechanisms, and their immunotherapeutic pros and cons. Around 500 structurally well-characterized anti-SARS-CoV-2 NmAbs were reported at the writing time (January 2021). All NmAbs bind respectively to SARS-CoV-2 S and exhibit high molecular neutralizing effects against wild-type and/or pseudotyped virus. Overall, we defined six NmAb groups blocking SARS-CoV-2 through different molecular neutralization mechanisms, from which five potential neutralization sites on SARS-CoV-2 S protein are described. Therefore, we suggest more efforts to be made toward the development of NmAbs-based cocktails to mitigate COVID-19.